Weaning Diet for Striped Murrel Channa striatus - M.A., Haniffa; A., Jesu Arockia Raj; S., Sridhar (Fishery Technology, 2025)
The early post larvae, late post larvae, fry and fingerlings of the different size groups of Channa striatus were reared from hatchling stage. The control group were supplied with plankton, whereas the experimental fish were provided with formulated diet and combined diet for a period of 90 days. 100% mortality was noticed in the early post larvae and late post larvae fed on formulated diets. Fry and fingerlings fed formulated diet showed significantly better survival (p <0.05) but poor growth. In terms of length and weight, fish fed on combined diet performed better compared to other treatments